Driven by Fear and Fun: How FOMO and Hedonic Motivation Shape Emotional Engagement and Participation in Sportainment Events - Rezi Muhamad Taufik Permana; Mochamad Malik Akbar Rohandi (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2026)
This study investigates the roles of Fear of Missing Out (FOMO) and hedonic motivation as antecedents of emotional engagement and continued participation intention in sportainment events. Unlike prior studies that examine these constructs in isolation or in Western metropolitan contexts, this research integrates both psychological drivers within a single affective mediation framework applied to an emerging Indonesian urban setting. A quantitative, cross‑sectional survey of 150 urban sportainment participants in Bandung was conducted using a structured Likert-scale questionnaire and analyzed via partial least squares structural equation modeling (PLS-SEM). Both FOMO and hedonic motivation positively and significantly influence emotional engagement, with hedonic motivation exhibiting a stronger effect. Emotional engagement, in turn, significantly predicts continued participation intention and fully mediates both antecedent effects. These findings reveal that while FOMO generates social momentum for attendance, hedonic experience quality is the principal driver of sustained emotional involvement and re-attendance and re-engagement. The results offer theoretically grounded and practically actionable insights for event designers and marketers in emerging urban markets.